Unusual histopathologies of the appendix - Jonas, Lusanda (My University, 2019)
ABSTRACT Objective To determine the incidence and type of unusual histopathology of the appendix. Method A retrospective review of histopathology reports of appendix specimens obtained during appendectomies done between January 2012 and December 2014 in the three academic hospitals of Johannesburg (CHBAH, CMJAH, and HJH). All specimens were examined by the National Health Laboratory Services (NHLS). Results A total of 2408 histopathology results were obtained from the national health laboratory system. 164 specimens were excluded because they were part of colonic resection for conditions unrelated to the appendicitis. From the 2244 specimens analyzed, 8.1%, 52.7% and 30.1% were due to normal appendix, acute appendicitis and complicated appendicitis respectively, and the incidence of unusual histopathology findings was 5.3% (119/2244). Of the 2244 specimens analysed the mean age was 25, 6 years (2-88yrs) and the gender distribution was 61.9 % males and 38.1% females. The most common unusual causes were parasites (37%) led by schistosomiasis (24.3%), followed by neoplasm (20%) and fibrous obliteration (14.2%). Conclusion Although uncommon (5.3%), the unusual causes of appendicitis may result in an adverse patient outcome and/or require specific treatment that may be overlooked if histopathology reports are not checked routinely.
A Research report submitted to the faculty of Health Sciences, University of the Witwatersrand, in fulfilment of the requirements for the degree of Master of Medicine (Surgery), Johannesburg, 2018